2021
DOI: 10.1111/jasp.12826
|View full text |Cite
|
Sign up to set email alerts
|

“Doing Good” versus “Being Good”: The interplay between pride appeals and regulatory‐focused messages in green advertising

Abstract: Many consumers feel proud of making green choices, which is of crucial relevance to explaining environmentally responsible behaviors. However, compared to other self‐conscious emotions, such as guilt and shame, little research attention has been paid to the role of pride in green consumerism. Through conducting two online experimental surveys, this research examined what features of a message induce the two facets of the emotion pride—authentic and hubristic—and how pride appeals interact with message frames h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 82 publications
(164 reference statements)
0
2
0
Order By: Relevance
“…low-level construal). Similarly, advertising studies have successfully applied a construal level matching effect to show that a construal level match between consumers’ mindsets and advertising messages increases receptivity to advertising messages (Lee et al , 2010) and boosts a product’s appeal (Spassova and Lee, 2013), thereby leading to positive consumer attitudes and behaviours (Chou and Lien, 2012; Hong et al , 2021; Lee et al , 2023; White et al , 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…low-level construal). Similarly, advertising studies have successfully applied a construal level matching effect to show that a construal level match between consumers’ mindsets and advertising messages increases receptivity to advertising messages (Lee et al , 2010) and boosts a product’s appeal (Spassova and Lee, 2013), thereby leading to positive consumer attitudes and behaviours (Chou and Lien, 2012; Hong et al , 2021; Lee et al , 2023; White et al , 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Even if promotion-focused people experience the loss of social connections, they are capable of making greater attempts to establish social re-engagement (Molden et al, 2009). In the context of emotion, a promotion focus is more responsive to an advertising message emphasising hubristic pride, an emotion associated with negative social behaviours, such as hostility, aggression, prejudice against others and interpersonal problems (Hong et al, 2021). Malicious envy involves negative social consequences, such as belittling or social differentiation from the target person.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…For example, following situations of social exclusion, the prevention system tends to focus on the actions that should not have been taken to avoid negative social consequences (Molden et al, 2009). In the specific context of emotion, a prevention focus would respond to an advertising message involving authentic pride, this being deemed a more pro-social emotion than hubristic pride (Hong et al, 2021). Benign envy should, therefore, appeal more to a prevention focus as it involves a strategy of levelling up by emulating the envied person and is deemed to be a relatively safer option in relation to social consequences.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the studies focused on consumer attitudes and intentions. For example, a more recent study by Hong et al (2021) found that more favorable attitudes and intention will be elicited when flattering with a hubristic pride ad (vs. an authentic ad) that is promotion-focused (vs. prevention-focused). Joshi and Kronrod (2020) revealed that brand names with silent consonants were perceived to be greener than names with voiced consonants, eliciting higher purchase intention.…”
Section: Green Advertisementmentioning
confidence: 99%